The analysis of employee performance measurement based on individual characteristics through promotion positon at PT Triteguh Manunggalsejati Business unit Makassar - Adiba Mubasyarah; Musran Munizu; Fauziah Umar (YUME : Journal of Management, 2020)
This study aims to find out and analyze how much influence the relationship between job promotion and individual characteristics on organizational commitment and employee performance. This type of research is quantitative research. Samples in the study used saturated samples of all employees of PT Triteguh Manunggalsejati Makassar Business Unit of 80 people consisting of various positions and jobs within the company environment. Data retrieval techniques using questionnaires. In processing this research data using SmartPLS3. Data analysis techniques used are path analysis. The results showed that individual characteristics have a positive effect on employees' performance, while the promotion of positions has no effect on employee performance at PT Triteguh Manunggalsejati Bisnis Unit Makassar. Keywords: job promotion, individual characteristics, organizational commitment, employee performance